No circular birefringence exists in a chiral medium: an analysis of single-mode refraction - Zhi-Juan Hu; Chun-Fang Li (New Journal of Physics, 2023)
Optical activity is one of the most fundamental phenomena in nature. The existing theoretical description of optical activity is the circular birefringence, proposed in 1825 by Fresnel. It states that the right-handed circularly polarized (RCP) and left-handed circularly polarized (LCP) waves in a chiral medium propagate at different velocities. Here we show that this is not the case. After obtaining the refraction and reflection coefficients of any elliptically polarized wave at the surface of an isotropic chiral medium, we derive the conditions for single-mode refraction. By means of the process of single-mode refraction, we demonstrate that both the refracted RCP and the refracted LCP waves at normal incidence can be expressed as a coherent superposition of a pair of orthogonal linearly polarized waves that are rotated simultaneously. As a result, they must propagate at the same velocity as the linearly polarized waves. A physical interpretation is also given in detail. In particular, we show that the state of polarization of any elliptically polarized wave in a chiral medium is rotated with propagation. Such a rotation amounts to the rotation of polarization bases without involving the change of the Jones vector. The rotation of the RCP and LCP waves, as special cases of elliptically polarized waves, results in two opposite phases as if they propagated at different phase velocities with their polarization states transmitted unchanged. These results demonstrate that the conventional characterization of optical polarization is incomplete. A further investigation into its new features is of great significance.